The Role of the Government in Tenure Issues and Land Management for Community Forest Development - Oktoyoki, Hefri; Ansiska, Paisal; Ifebri, Rihan (GEOFORUM, 2022)
Community forests, by definition, are located on privately owned land and are managed by the local people, so there should be no tenure issues related to them. However, several factors can trigger land conflicts. First, community forests are sometimes established under profit-sharing schemes between different landowners and forest farmers who work the land. Still, the agreements are often informal and need to be in accordance with the Basic Agrarian Law (UUPA). Second, community forests planted on idle state-owned land have the potential to cause conflicts between the government and the people. Third, there are conflicts between different managers of community forests. Solutions to prevent and resolve potential tenure conflicts in community forests include: first, providing education and assistance and resolving disputes through negotiation and mediation. Second, state-owned land can be converted into private property (either for individuals or groups), and the land can be designated as HTR (Community Plantation Forests) and HKm (Community Forests). Third, encouraging the clear demarcation of land/forest boundaries used, creating a proportional social structure within the production dimension, ensuring clear land ownership and supervision, and strengthening the institutions of community forest farmers by the gove